Government expenditures, social outcomes, and marginal productivity of agricultural inputs: a case study for Tanzania - Allen, Summer L.; Badiane, Ousmane; Ulimwengu, John M. (International Food Policy Research Institute, 2012)
In an effort to inform strategic options to improve agricultural productivity, we examine the impact of social service expenditures on the marginal productivity of agricultural inputs. Increasing agricultural productivity is often advocated as a way to reduce poverty, especially in sub-Saharan Africa, where many people still rely on agriculture as their main source of income. Unfortunately, limited national budgets are often focused on meeting short-term needs rather than on making longer-term, growth-enhancing investments in agriculture and rural areas. Using Tanzania as a case study, this research investigates the direct and indirect impacts of district-level health and education expenditures on marginal productivities of agricultural inputs through education and health outcomes. This approach uses recently-released data for Tanzania and health and education spending data as well as an innovative combination of approaches including a general covariance structure model and a mixed linear model to allow for district-level heterogeneity. Our results suggest a significant and nonlinear relationship between social outcomes and social expenditures and point to the importance of these outcomes in productivity. Marginal productivities of inputs are significant and confirm the validity of a heterogeneous technology approach. As expected, labor productivity, in particular, responds significantly to health and education outcomes. The findings also point to the importance of controlling for intra-country socioeconomic and agro-climatic heterogeneity.